Tahapan perkembangan iman: perspektif james w. Fowler - Wotan, Handhala Al Ashshidie (Maliki Interdisciplinary Journal, 2025)
Faith development is a fundamental aspect of human life, which is influenced by cognitive, emotional, social and cultural factors. This article discusses James W. Fowler's theory of faith development and explores its application in the context of modern life. The theory divides faith development into seven stages that reflect changes in the way individuals understand and live out their spiritual beliefs. The results show that Fowler's theory provides a deep understanding of how faith develops as individuals grow, although it is still limited in its applicability outside the context of Christianity. In addition, external factors such as social media, technology and social dynamics also influence faith development. Therefore, further research is needed to expand the scope of this theory to make it more relevant to different religious and cultural backgrounds and spiritual challenges in the modern era.